HUBUNGAN AKTIVITAS BERSAMA TEMAN SEBAYA DENGAN PERILAKU KENAKALAN REMAJA DI SMK BHAKTI HUSADA KUNINGAN - Ani Nurhaeni (JURNAL KESEHATAN INDRA HUSADA, 2020)
Juvenile delinquency is a social pathological symptom in adolescents caused by a form of social neglect, resulting in adolescents developing aberrant behavior. One of the other factors that cause the happening of juvenile delinquency is the association factor of peers. Joining teenagers with peers will result in changes. Changes that occur are in terms of activity. The purpose of this study was to determine the relationship between peer activities with juvenile delinquency behavior. This research type is correlation with quantitative method and cross sectional approach. The population in this study are all students in SMK Bhakti Husada Kuningan and sampling using purposive sampling method amounted to 50 people. Taking the research data using questionnaire. The results showed that most respondents had peer activity in good category (42%) and juvenile delinquency behavior in low category (48%). Statistical test results obtained ρ value <α with value (p = 0,000) which indicates that Ha accepted means there is a relationship between peer activity with behavior of juvenile delinquency At Bhakti Husada School Kuningan. The importance of facilities in order to minimize the happening of juvenile delinquency by activating extracurricular activities both in academic and non academic fields.